Epigenetic regulation of interleukin-8, an inflammatory chemokine, in osteoarthritis. Issue 11 (November 2015) - Takahashi, A.; de Andrés, M.C.; Hashimoto, K.; Itoi, E.; Oreffo, R.O.C.
Summary: Objective: To determine whether altered IL8 methylation status is associated with increased expression of IL8 in human osteoarthritic (OA) chondrocytes. Methods: IL8 expression levels and the percentage CpG methylation in human chondrocytes were quantified by qRT-PCR and pyrosequencing in OA patients and in non-OA osteoporotic controls. The effect of CpG methylation on IL8 promoter activity was determined using a CpG-free vector; co-transfections with expression vectors encoding nuclear factor-kappa B (NF-κB), AP-1 and C/EBP were subsequently undertaken to analyse for IL8 promoter activity in response to changes in methylation status. Results: IL8 expression in OA patients was 37-fold higher than in osteoporotic controls. Three CpG sites in the IL8 promoter were significantly demethylated in OA patients. Multiple regression analysis revealed that the degree of methylation of the CpG site located at −116-bp was the strongest predictor of IL8 expression. In vitro DNA methylation was noted to decrease IL8 promoter basal activity. Furthermore, NF-κB, AP-1 and C/EBP strongly enhanced IL8 promoter activity whilst DNA methylation inhibited the effects of these three transcription factors. Conclusions: The present study demonstrates the key role of DNA methylation status on the expression of IL8 in human chondrocytes. We demonstrate a quantitative relationship between percentage methylation and gene expression within clinical samples. These studies provide direct evidence linking the activation of IL8, DNA demethylation and the induction of the OA process with important therapeutic implications therein for patients with this debilitating disease.